Cinnamic Aldehyde Inhibits Lipopolysaccharide-Induced Chondrocyte Inflammation and Reduces Cartilage Degeneration by Blocking the Nuclear Factor-Kappa B Signaling Pathway - Chen, Pu; Ruan, Anmin; Zhou, Jun; Huang, Liuwei; Zhang, Xiaozhe; Ma, Yufeng; Wang, QingFu (Frontiers in Pharmacology, 2020)
Osteoarthritis (OA), as one of the top-10 causes of disability, is characterized by inflammation of synovial membrane, progressive destruction of articular cartilage. Cinnamic aldehyde (CA), an α, β-unsaturated aldehyde extracted from the traditional Chinese herbal medicine cinnamon, has been reported to have anti-inflammatory, antioxidant, and anticancer properties. However, the anti-inflammatory effect of CA in OA remains unclear. The purpose of the present study was to investigate the effects of CA on inflammation and cartilage degeneration in OA. A CCK-8 assay was performed to assess the potential toxicity of CA on cultured human OA chondrocytes. Following treatment with lipopolysaccharide (LPS) and CA, the production of proinflammatory cytokines, including interleukin (IL)-1β, IL-6 and tumor necrosis factor-α (TNF-α), was evaluated using quantitative real-time polymerase chain reaction (RT-qPCR) analysis, enzyme linked immunosorbent assay (ELISA), and western blotting (WB). The production of matrix metalloproteinase-13 (MMP-13) and a disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS-5) were also examined using RT-qPCR and WB. Furthermore, to investigate the potential anti-inflammatory mechanism of CA, biomarkers of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway (p65, IKB-α) were detected by WB. Results demonstrated that CA significantly inhibited the expression of IL 1β, IL-6, TNF-α, MMP-13, and ADAMTS-5 in LPS-induced OA chondrocytes. CA dramatically suppressed LPS-stimulated NF-κB activation. Collectively, these results suggest that CA treatment may effectively prevent OA.